A specific exercise strategy reduced the need for surgery in subacromial pain patients. Issue 19 (26th June 2014) - Hallgren, Hanna C Björnsson; Holmgren, Theresa; Öberg, Birgitta; Johansson, Kajsa; Adolfsson, Lars E
Abstract : Background and purpose: A programme based on eccentric exercises for treating subacromial pain was in a previous study found effective at 3-month follow-up. The purposes of the present study were to investigate whether the results were maintained after 1 year and whether the baseline Constant-Murley score, rotator cuff status and radiological findings influenced the outcome. Patients and methods: 97 patients on the waiting list for arthroscopic subacromial decompression had been randomised to a specific exercise programme or unspecific exercises (controls). After 3 months of exercises, the patients were asked whether they still wanted surgery and this option was available until a 1-year follow-up. 1 year after inclusion or 1 year after surgery, the number of patients who decided to have surgery in each group was compared. The choice of surgery was related to the baseline Constant-Murley score, ultrasound and radiographs taken at inclusion. Results: All patients had improved significantly (p<0.0001) in the Constant-Murley score at the 1-year follow-up. Significantly more patients in the control group decided to have surgery (63%) than those in the specific exercise group (24%; p<0.0001). Patients who decided to have surgery had a significantly lower baseline Constant-Murley score and more often a full-thickness tear. Patients with partial tears did not differ from those with intact tendons. Interpretation: The positive short-term results of specific exercises were maintained after 1 year, and this exercise strategy reduces the need for surgery. Full-thickness tear and a low baseline Constant-Murley score appear to be a predictive marker for a less good outcome. Trial registration number: Clinical trials NCT01037673 .